003.1 Correlates of repeat anorectal infections among men who have sex with men. (13th September 2015) - Kong, FYS; Tabrizi, S; Fairley, CK; Phillips, S; Huston, W; Vodstrcil, LA; Fehler, G; Chen, M; Bradshaw, CS; Hocking, JS
Abstract : Introduction: There is increasing concern about azithromycin treatment failure for rectal chlamydia. Higher organism loads have been reported at the rectal site compared to other sites (genital/oral) and higher organism load may be associated with treatment failure in women, but little data are available among men who have sex with men (MSM). This study examined the association between organism load and repeat rectal chlamydia infection in order to investigate possible mechanisms for treatment failure. Methods: Stored rectal chlamydia positive samples from men attending Melbourne Sexual Health Centre between July 2008 to October 2013 were analysed for organism load and chlamydia serovar. Men were included if they had a follow-up test within 100 days of the index infection. Results: There were 292 chlamydia positive index rectal swabs available for analysis. Organism load and serovar were assessable for 284 swabs -– 44 cases had one repeat positive result, 5 cases had two repeat positives and 181 MSM had a negative result within 100 days of their index positive result. Among the 230 index infections, 33% were serovar G, 30% were D, 15% were J, 9% were E, 7% were L2, 3% were B and 2% were F. The cumulative incidence of repeat rectal chlamydia within 100 days was 21%. Among those men who had a repeat positive result, all but three (3%) were the same serovar. Organism load was higher in index cases of men who had a repeat infection compared with those who did not (p < 0.01). Conclusion: Repeat rectal chlamydia is common within 100 days among MSM attending MSHC. Most repeat infections were of the same serovar suggesting these infections were either treatment failure or re-infection from an infected partner. High organism load was associated with repeat infection suggesting a possible role in treatment failure. Disclosure of interest statement: None.